Architecture and Resilience : Interdisciplinary Dialogues - Trogal, Kim; Bauman, Irena; Lawrence, Ranald; Petrescu, Doina; Taylor and Francis (Boca Raton, FL : Routledge, 2018)
Resilience will be a defining quality of thetwenty-first century. As we witness the increasingly turbulent effects of climate change, the multiple challenges of resource depletion and wage stagnation, we know that our current ways of living are not resilient. Our urban infrastructures, our buildings, our economies, our ways of managing and governing are still too tightly bound to models of unrestrained free-market growth, individualism and consumerism. Research has shown that the crises arising from climate change will become increasingly frequent and increasingly severe. It is also known that the effects of climate change are not evenly distributed across places and people, and neither are the resources needed to meet these challenges. We will need specific responses in place that engage with, and emerge from, citizens ourselves. This volume takes resilience as a transformative concept to ask where and what architecture might contribute. Bringing together cross-disciplinary perspectives from architecture, urban design, art, geography, building science and psychoanalysis, it aims to openup multiple perspectives of research, spatial strategies and projects that are testing how we can build local resilience in preparation for major societal challenges, defining the position of architecture in urban resilience discourse.
1. Introduction: Architecture and Resilience on a Human ScaleKim Trogal, Irena Bauman, Ranald Lawrence and Doina Petrescu Dialogue: Narratives of Resilience 2. Collective documenting of extreme urban transformations; evidence of urban resilience during war in Sarajevo (1992-1996) Armina Pilav 3. Future Works: stories resilience and resourcefulness Renata Tyszczuk & Julia Udall 4. Building and Bearing Witness in Calais. An interview with Grainne Hassett Grainne Hassett with Irena Bauman Dialogue: Community resilience and the right to housing 5. Social architectures of age-friendly community resilience: lessons from niche intentional community development Helen Jarvis 6. Building eco-homes for all: inclusivity, justice and affordability Jenny Pickerill 7. Micro-resilience and justice in So Paulo Beatrice De Carli Dialogue: New pedagogies of resilience 8. Tackling climate change: comparing studio approaches in Sheffield and Cape Town Ranald Lawrence and Kevin Fellingham 9. Architecture of multiple authorship: beyond the academic year Sandra Denicke-Polcher 10. Provocateurs or Consultants? The role of Sheffield School of Architecture in the co-production of Castlegate An Interview with Carolyn Butterworth Carolyn Butterworth with Ranald Lawrence Dialogue: Challenging Climate Denial 11. Building resilience in the built environment Susan Roaf 12. The new imagination in a culture of uncare Sally Weintrobe 13. Management before fabric An interview with Irena Bauman Irena Bauman with Ranald Lawrence and Kim Trogal Dialogues: Resilience Ethics and Interdependence 14. Resilient subjects: on feminist practice Elke Krasny and Meike Schalk 15. Resilience as interdependence: learning from the care ethics of subsistence practices Kim Trogal 16. The Organic Internet Panayotis Antoniadis 17. Living resiliency: between planning and the grassroots. An interview with Daniel DOca Daniel DOca with Kim Trogal and Doina Petrescu Dialogues: Scales of resilience concerning the city, the region and globalization 18. Globalization, Risk, and Resistance: The production of new spaces of conflict and resilience Axel Becerra Santacruz 19. Learning from New Orleans: Social resilience for urban ecosystems Marchella Del Signore & Cordula Roser Gray 20. From city policy to neighbourhood. An interview with Tina Saaby Tina Saaby with Irena Bauman 21. Commons-Based Urban Resilience: an interview with Constatin Petcou and Doina Petrescu - atelier darchitecture autogre (aaa) aaa with Kim Trogal Index.
Includes bibliographical references and index.
Also available in print format.
Keywords: ARCHITECTURE / Urban & Land Use Planning; city; climate change; ecology; energy; environment; geography; practice; sustainability; theory; urban; Architecture and climate; Sustainable architecture; Architecture and society; Electronic books